Scaling knowledge and innovations for food and nutrition security— Tackling dilemmas and blind spots - Koerner, Jana; Lubberink, Rob; Lammers, Ellen; Winter, Daniëlle de (2021)
Global food systems need to become more sustainable, resilient and inclusive. To accelerate this transition, there is a need for scaling innovative strategies for improved Food and Nutrition Security (FNS), particularly for the poor and marginalised. Scaling, however, is not a straightforward or value-free process. The synthesis study examined which dilemmas influence Research for Impact projects that seek to contribute to FNS outcomes at scale, and how blind spots in scaling research and practice are tied to these dilemmas. Being aware of and tackling these blind spots at an early stage contributes to ‘responsible scaling’: not only focusing on technical and socio-economic, but also on ethical considerations about who will benefit or lose out. The findings presented in the full paper are based on insights from ten interdisciplinary research projects funded by NWO-WOTRO that were carried out in countries in East, Southern and the Horn of Africa between 2014–2020.